2019
DOI: 10.3390/vision3030037
|View full text |Cite
|
Sign up to set email alerts
|

Eye Behavior During Multiple Object Tracking and Multiple Identity Tracking

Abstract: We review all published eye-tracking studies to date that have used eye movements to examine multiple object (MOT) or multiple identity tracking (MIT). In both tasks, observers dynamically track multiple moving objects. In MOT the objects are identical, whereas in MIT they have distinct identities. In MOT, observers prefer to fixate on blank space, which is often the center of gravity formed by the moving targets (centroid). In contrast, in MIT observers have a strong preference for the target-switching strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
(173 reference statements)
3
18
0
Order By: Relevance
“…Obtaining a set size effect despite a similar number of occlusions in the OB-2, OB-4, OC-2, and OC-4 conditions is due to an increase in the frequency of target visit by increasing set size. This is in line with previous research, which showed that observers frequently switch fixations between each target and the centroid of multiple targets during multiple object tracking (MOT), so that there are more saccades to targets as the set size increases (Hyönä et al, 2019).…”
Section: Are Rescue Saccades Helpful In Tracking?supporting
confidence: 92%
See 1 more Smart Citation
“…Obtaining a set size effect despite a similar number of occlusions in the OB-2, OB-4, OC-2, and OC-4 conditions is due to an increase in the frequency of target visit by increasing set size. This is in line with previous research, which showed that observers frequently switch fixations between each target and the centroid of multiple targets during multiple object tracking (MOT), so that there are more saccades to targets as the set size increases (Hyönä et al, 2019).…”
Section: Are Rescue Saccades Helpful In Tracking?supporting
confidence: 92%
“…According to the literature, even 2-year-old infants are able to track more than one moving object (Cheng et al, 2019), and this ability improves as they grow older. In cognitive science, MTT experiments are used to study behavioral and/or neural aspects related to dynamic attention, short-term memory, and eye movements (for reviews, see Hyönä et al, 2019;Kamkar et al, 2020;Meyerhoff et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Gaussian emission distribution can be easily generalized for non-elliptical objects. The model might even be adaptable to a multiple object tracking setting by using centroids of sets of objects rather than the objects themselves Seiffert, 2008, 2010;Hyönä et al, 2019).…”
Section: Hidden Markov Modelmentioning
confidence: 99%
“…As noted previously, this may require introducing additional states in the HMM corresponding to subsets of visible objects. Extensive research in the multiple object and multiple identity tracking paradigms suggests that gaze may be concentrated around the centroid of the tracked objects, with occasional looks to the individual tracked objects (Hyönä et al, 2019). This could be incorporated into the HMM by adding a state whose emission distribution is Gaussian around the centroid, or a mixture of a Gaussian around the centroid and Gaussians around the individual objects.…”
Section: Extension To Natural Scenes With Automatic Object Detectionmentioning
confidence: 99%
“…Analyzing the eye movements of the subjects helps better investigate this; if MOT is a parallel mechanism, the subjects should rarely look at the targets, while if MIT is a serial mechanism, subjects should focus on targets one after another. Recently, a review of eye behavior studies for both MOT and MIT is provided in [35].…”
Section: Mit Versus Motmentioning
confidence: 99%